2014
DOI: 10.3390/ijerph110707242
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence of Canine Leptospirosis in Switzerland

Abstract: A marked increase in canine leptospirosis was observed in Switzerland over 10 years with a peak incidence of 28.1 diagnosed cases/100,000 dogs/year in the most affected canton. With 95% affected dogs living at altitudes <800 m, the disease presented a seasonal pattern associated with temperature (r2 0.73) and rainfall (r2 0.39), >90% cases being diagnosed between May and October. The increasing yearly incidence however was only weakly correlated with climatic data including number of summer (r2 0.25) or rainy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
140
3
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(170 citation statements)
references
References 45 publications
14
140
3
8
Order By: Relevance
“…In that study, 34% of the dogs showed positive Leptospira antibody titres, with seroconversion to other serovars, e.g., Bratislava, Australis, Icterohaemorrhagiae, Pomona and Grippotyphosa, being common. Moreover, in a survey of 259 dogs from Switzerland over a 10-year-period before the introduction of the tetravalent vaccine, only 12.3% of the dogs showed seropositivity to serovar Canicola [5]. We cannot conclude from the present data whether the positive MAT titres to Canicola were due to previous vaccination or natural exposure to this serovar.…”
Section: Discussioncontrasting
confidence: 59%
“…In that study, 34% of the dogs showed positive Leptospira antibody titres, with seroconversion to other serovars, e.g., Bratislava, Australis, Icterohaemorrhagiae, Pomona and Grippotyphosa, being common. Moreover, in a survey of 259 dogs from Switzerland over a 10-year-period before the introduction of the tetravalent vaccine, only 12.3% of the dogs showed seropositivity to serovar Canicola [5]. We cannot conclude from the present data whether the positive MAT titres to Canicola were due to previous vaccination or natural exposure to this serovar.…”
Section: Discussioncontrasting
confidence: 59%
“…Serovar Bratislava has been isolated from a wide range of domestic and wild animals including hedgehogs, rats, sheep and horses in Ireland, with which dogs can come into contact or share environments (Ellis and others 1983, Hathaway and others 1983). Seropositivity to serogroup Australis can be associated with severe clinical disease in dogs (Mastrorilli and others 2007, Mayer-Scholl and others 2013, Major and others 2014). At the same time it has been postulated that dogs may also serve as a maintenance host for serovar Bratislava (Ellis 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of leptospirosis range from a mild illness to an acute, life‐threatening multisystemic disorder . Leptospirosis is commonly associated with acute kidney injury, liver dysfunction, pulmonary involvement, and, less commonly, a hemorrhagic syndrome . In previous retrospective studies of dogs, this hemorrhagic syndrome was characterized by the occurrence of hematuria (with an incidence of 6–31%), melena (3–9%), petechial hemorrhages (11.5–12.5%), hemorrhagic nasal discharge (19%), hematochezia (3%), and spontaneous hemorrhage (2.5%) …”
mentioning
confidence: 99%